Parking issues and policies - Mulley, Corinne; Ison, Stephen (Emerald, 2014)
Travel by car invariably involves the use of a car parking space at the start and end of the journey, the provision of which impacts on travel demand and travel behaviour. The presence or absence of parking at the destination also has significant implications for the demand for public transport. The impact of parking on mode share and travel demand more generally thus has implications for transport and sustainability. Parking has been extensively used as a means of managing the demand for car travel, be it by use of parking pricing, regulation or parking supply via polices such as park and ride. Given the ubiquitous nature of parking in our cities, there is a relative lack of research at least when compared to measures such as road pricing of which much has been written but of which there are few schemes in existence world-wide. This book advances the debate with respect to parking; covering the issues of supply and demand, the various policy measures, namely economic, regulatory, regional wide or organisational. Carefully selected case studies highlight specific examples with industry and research implications. It concludes with a piece about the future direction of parking policy.
Includes index.
Keywords: Automobile parking.; Transportation -- Industries.; elektronické knihy; electronic books